Malignant nodular fasciitis, a rare manifestation of a benign disease: case report - Aboulafia, Albert J.; Liddy, Nicole; Zeitlinger, Lauren; Molavi, Diana W.; Murali, Sudarsan; Aboulafia, David (Frontiers in Oncology, 2026)
CaseNodular fasciitis is a common benign tumor resulting from reactive proliferation of fibroblasts and myofibroblasts. It most often presents as a firm and solitary lump in the subcutaneous fat layer or fascia adjacent to muscles in the extremities. Because of its rapid growth and high cellularity, it may mimic soft-tissue sarcoma, but it is self-limiting, often resolving with fibrosis. The evolution of benign nodular fasciitis to malignant nodular fasciitis is distinctly uncommon, and only a handful of cases have been reported in the medical literature. Herein we describe the case of a woman with a 21-year history of multifocal nodular fasciitis superimposed on malignant nodular fasciitis. Her course has been characterized by rapid tumor growth and widespread dissemination. Over the course of 2l years she underwent multiple surgical procedures. Ultimately, molecular studies demonstrated a fusion of protein phosphatase 6 regulatory subunit 3 (PPP6R3)–ubiquitin specific peptidase 6 (USP6), suggesting an oncogenic mechanism despite classic histologic features of benign nodular fasciitis with aggressive behavior. She subsequently received systemic therapy, initially with temozolomide and later pazopanib, followed by sunitinib. With the later medication she has achieved a good response of now more than 18 months. This case illustrates the importance of molecular drivers of cancer in a benign soft-tissue tumor and the potential to offer targeted therapies to extend patient survival. This rare case highlights the potential malignant behavior of nodular fasciitis associated with PPP6R3-USP6 fusion.